A new species of Lepiota (Agaricaceae) from Punjab, Pakistan - Niazi, Abdul Rehman; Asif, Muhammad; Izhar, Aiman; Khalid, Abdul Nasir (Phytotaxa, 2021)
During our surveys of fungi of some areas adjacent to the Cholistan desert, Punjab, Pakistan, we collected a new species in Lepiota sect. Echinatae. It was found on loamy soil under Vachellia nilotica and is described and illustrated as new based on the distinct morphology and ITS nrDNA analysis. The new species, Lepiota haroonabadensis, is characterized macroscopically by a light yellowish orange pileus covered with brown squarrose scales, bright yellowish to yellowish red stipe with pale yellow spiny scales, and rudimentary annulus; and microscopically by ellipsoid basidiospores, narrowly clavate to clavate cheilocystidia, cylindrical to sub-cylindrical or ellipsoidal elements of the pileus covering and cylindrical to globose elements of the stipe covering. A full description, color photos, line illustrations and a phylogenetic tree to show the position of the new species are provided.